2021
DOI: 10.1002/anie.202101278
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Design Strategy to Construct Smart Fluorescent Probes for the Precise Tracking of Senescence

Abstract: The tracking of cellular senescence usually depends on the detection of senescence‐associated β‐galactosidase (SA‐β‐gal). Previous probes for SA‐β‐gal with this purpose only cover a single dimension: the accumulation of this enzyme in lysosomes. However, this is insufficient to determine the destiny of senescence because endogenous β‐gal enriched in lysosomes is not only related to senescence, but also to some other physiological processes. To address this issue, we introduce our fluorescent probes including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“… 40 Alternatively, Gao et al reported the use of β-Gal purified from Aspergillus oryzae (β-Gal/ A. oryzae ) with a more acidic working pH range of 4.0–5.0, which is more similar to that of lysosomes. 49,50 As a result, we attempted the detection of β-Gals isolated from different origins (bacterium or fungus) in order to examine the sensitivity of the AIE-based glycoclusters developed.…”
Section: Resultsmentioning
confidence: 99%
“… 40 Alternatively, Gao et al reported the use of β-Gal purified from Aspergillus oryzae (β-Gal/ A. oryzae ) with a more acidic working pH range of 4.0–5.0, which is more similar to that of lysosomes. 49,50 As a result, we attempted the detection of β-Gals isolated from different origins (bacterium or fungus) in order to examine the sensitivity of the AIE-based glycoclusters developed.…”
Section: Resultsmentioning
confidence: 99%
“…oryzae) with a working pH range (4.0-5.0) more similar to that expressed in human cells. [62][63] As a result, we attempted the detection of the β-Gal isolated from both bacteria in order to examine the sensitivity of the AIE-based glycoclusters developed. TD-Gal6 was incubated separately with β-Gal/E.…”
Section: Resultsmentioning
confidence: 99%
“…One of the best characterized features for senescence is the positive staining for SA-β-gal at PH6, which indicates a marked expansion of lysosomal compartment in functional-altered senescent cells [ 56 ]. SA-β-gal staining was first applied to recognize senescent fibroblast in aging skin and is still the most widely used markers to detect senescent cells nowadays [ 57 ].…”
Section: Evidence Of Cellular Senescence In Cardiovascular Diseasesmentioning
confidence: 99%
“…In addition to the senescent fibroblasts, cardiomyocytes senescence can also exert anti-fibrotic effects and regulate the surrounding cells via activating SASP complex. For example, Cui et al demonstrated that the senescent cardiomyocytes improved heart function via activating GATA4-dependent CCN1 secretion in ischemic heart [ 56 ]. CCN1 is an important component of SASP, which can restrict fibrosis and improve cardiac dysfunction postinfarction.…”
Section: Consequence Of Cellular Senescence In Cardiovascular Diseasesmentioning
confidence: 99%